Analisis Implementasi Kompensasi Lingkungan Pembangunan Infrastruktur: Studi Kasus di Kota Makassar - Rizal Pauzi Rizal (Development Policy and Management Review (DPMR), 2021)
Environmental compensation was the project’s executive obligation to be implemented. This was according to government policies both central and regional to achieve sustainable development. This research aimed to analyze the implementation of the environmental compensation on Andi Pangeran Pettarani Makassar highway construction. This research was conducted at the location of Andi Pangeran Pettarani highway construction project, which was located in Makassar. The key informants were the project’s executive, as well as the community who were the complementary informants. This research used qualitative approach, focused on the implementation of environmental compensation of Andi Pangeran Pettarani highway construction. As for the research design, the researcher used Case Study Research Design. The result of the research showed that the implementation of environmental compensation of Andi Pangeran Pettarani highway construction had been running optimally. Furthermore, (1) The availability of time was already established by terms and resources commitment from PT Bosowa Marga Nusantara that had budgeted 1.5 billion for the provision of new Green Open Space (Ruang Hijau Terbuka) and PT Nusantara Infrastruktur (NI) that had planted 2000 trees collaborated with the Ward Service of Makassar. (2) The implemented policies based on provisions of act 26 in 2007 about space governance, The Minister of Public Works Reguation Number 5 on 2008 and The Makassar Mayor’s rules number 69 in 2016 about User License (3) The comprehension and agreement only occurs between the project executive and the Makassar’s government, but there was no agreement involving the community. It could be seen that there was no public consultation and the rise of complaints from environmental observers. Keywords: Implementation; Compensation; Green Open Space